Նոր Ջուղայի վաճառականները՝ որպես Իրանի և Արևմտյան Եվրոպայի միջև առևտրի միջնորդներ - Ք. Վ. Պապիկյան (ՀՀ ԳԱԱ հրատ.)
Согласно сведениям летописцев XVII века (Закария Канакерци, Аракел Даврижеци, Закария Агулеци), иранским шахом Аббасом I было организовано массовое насильственное переселение армян в Иран. Благодаря торговой деятельности армянского купечества армянский торговый капитал (капитал ходжей) был сосредоточен в поселке Новая Джуга (Джульфа), основанном переселенцами из разных районов Армении в южной части города Исфахан. Купцы из Новой Джуги являлись посредниками в торговле между Ираном и Западной Европой. According to the historiographers of the 17th century (Zakaria Kanakerzi, Arakel Davrizhetsi, Zakaria Aguletsi), the Iranian Shah Abbas I organized a massive forced migration of Armenians to Iran. Thanks to the trade activities of the Armenian merchants, the Armenian commercial capital (Khoja capital) was concentrated in the village of New Dzhuga (Julfa), founded by settlers from different regions of Armenia in the southern part of the city of Isfahan. Merchants from New Jugha were mediators in trade between Iran and Western Europe.
Keywords: History; D History